2019
DOI: 10.31234/osf.io/wyvnm
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Associations of cigarette smoking with gray and white matter in the UK Biobank

Abstract: Chronic cigarette smoking is associated with increased risk for myriad health consequences including cognitive decline and dementia, but research on the link between smoking and brain structure is nascent. We assessed the relationship of cigarette smoking (ever smoked, cigarettes per day, and duration) with gray and white matter using the UK Biobank cohort (gray matter N = 19,615; white matter N = 17,760), adjusting for numerous demographic and health confounders. Ever smoked and duration were associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 31 publications
2
11
0
Order By: Relevance
“…At the brain level, grip strength revealed mostly significant positive correlations with brain volume, which aligns with previous evidence at the global level [23]. As the global GMV is a general reflection of health status and GM atrophy is a signature of neurodegeneration [27,28], the identified association pattern may suggest that having stronger muscular strength also relates to better overall brain health [22]. Furthermore, given that many regional GM associations reach a significant effect after controlling for the total ICV, it implies that grip strength may exert a region-specific beneficial effect on brain structure.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…At the brain level, grip strength revealed mostly significant positive correlations with brain volume, which aligns with previous evidence at the global level [23]. As the global GMV is a general reflection of health status and GM atrophy is a signature of neurodegeneration [27,28], the identified association pattern may suggest that having stronger muscular strength also relates to better overall brain health [22]. Furthermore, given that many regional GM associations reach a significant effect after controlling for the total ICV, it implies that grip strength may exert a region-specific beneficial effect on brain structure.…”
Section: Discussionsupporting
confidence: 89%
“…These findings increased current understanding on the use of grip strength not only as a proxy of physical fitness but also as a malleable indicator for health status in detecting early impairment of specific domains. Unsurprisingly, some of the associations were small and likely due in part to the fact that we controlled for numerous demographic, socioeconomic, and anthropometric measures that are expected to co-occur with health status [50,51] and muscular strength [27]. Consequently, the association effects should be interpreted as the relevance of grip strength to these mental health outcomes beyond the contribution of covariates [28].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Moreover, smoking duration linked with reduced total volume of white matter. It is also associated with reduction in fractional anisotropy in cingulate gyrus 64 . Lamb/mutton intake was also positively associated with brain-PAD in some tract groups.…”
Section: Discussionmentioning
confidence: 96%
“…Neuroimaging studies of cigarette smoking and brain regions of interest (ROIs) consistently show that higher levels of cigarette smoking are related to thinner cortex and smaller subcortical volumes [4][5][6][7][8][9]. A UK Biobank study comprising approximately 20 000 participants reported smaller total gray matter volume in long-term smokers [10]. Smokers seeking treatment for tobacco use have shown smaller cerebellar volumes relative to nonsmokers [11].…”
Section: Introductionmentioning
confidence: 99%